Description of the male of Sphallopterus batesi Fragoso, 1982 (Coleoptera: Cerambycidae: Cerambycini), with biogeographical considerations - Taboada-Verona, Carlos; Torrez, Antonio Rodriguez; Arana, Marcelo D. (Zootaxa, 2018)
The male of Sphallopterus batesi Fragoso, 1982 is described for the first time. New records of geographic distribution are presented for Bolivia (new country record) and Brazil, and the biogeography of the species is analysed.